Pengaruh suplementasi zink terhadap parameter hematologi atlet sepatu roda setelah latihan endurance - Mirza Hapsari Sakti Titis Penggalih; Mustika Cahya Nirmala Dewinta; Choiri Khumaidah Fikriyah; Noni Kustia; Assyifatu Rahmah Zada; Zaenal Muttaqien Sofro; BJ Istiti Kandarina (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: In sports such as roller skates, endurance can lead to increased inflammation and muscle cell damage, free radical formation, and zinc excretion from sweat and urine that affect the increased redistribution of zinc from blood to tissue. This mechanism causes a decrease in blood zinc levels, erythrocyte numbers and hemoglobin concentrations, increased leukocyte counts and the body’s oxidative stress parameters that have an impact on the athlete’s performance decline. Zinc supplementation may be given to maintain the athlete’s hematologic parameters during endurance exercise.Objectives: To examine the effect of zinc supplementation on serum zinc level, hemoglobin concentration, erythrocyte and leukocyte counts, and blood MDA level of skate athletes after endurance exercise.Method: This study was an experimental clinical trial using pre and post-test designs on 8 athletes incorporated in the pre-PON DIY Wheels Team. The study was conducted in two periods, one week of endurance exercise without zinc supplementation and one week of endurance exercise with 30 mg/d of zinc supplementation. Blood sampling was performed on the seventh day of each period, before and after endurance training.Results: There was a decrease in erythrocytes and hemoglobin concentration, and a significant increase in leukocyte count after endurance training in both periods (p<0.05), but no significant difference in serum zinc levels and malondialdehid (MDA) levels after endurance training in both periods (p>0.05). Although there were no significant differences in all athlete hematologic parameters between two treatments (p>0.05), there was an improvement in serum zinc levels, hemoglobin concentrations, erythrocyte, and leukocyte counts.Conclusion: Zinc supplementation 30 mg/day for one week did not have a significant effect on the athlete’s hematology parameters after endurance exercise.